Synthesis of ZnO/NiO Thin Film on Fluorine-doped Tin Oxide (FTO) by Two Step Electrodeposition as Photoanode of a Solar Cell - Ines Ayu Handayani; Abdul Haris; Didik Setiyo Widodo (Jurnal Kimia Sains dan Aplikasi, 2018)
Synthesis of ZnO/NiO Thin Film on Fluorine-doped Tin Oxide (FTO) by Two Step Electrodeposition has been conducted. The film was used as a photoanode of a solar cell. Synthesis was performed by two step electrodeposition with FTO as anode and carbon rod as cathode. NiO was firstly electrodeposited at 2.4 V from 0.2 M of NiCl2 solution at pH 11, 70°C, under stirring of 250 rpm after air bubbling. Second step, ZnO was electrodeposited at 2.6 V from precursor Zn(NO3) 0.2 M, pH 12, 70°C with air bubbling and stirring of 250 rpm. Product was then calcined at 450°C for 2 hours followed with XRD characterization. A solar cell was constructed by utilizing the ZnO/NiO film as photoanode related to aluminium plat as cathode. Data resulted showed that the efficiency in NiO deposition was 39.4% with mass of 8 mg and 16 µm in thin film size. Efficiency in ZnO deposition was 12.7% with mass of 14.7 mg and 11 µm in thin film size. XRD data informed that NiO and ZnO were thin filmed to FTO substrate with powder size of 30.31 nm and ZnO of 21.07 nm. Photovoltaic activity test with illuminating UV light 15 W onto the film resulted in that the average voltages of 240.93 mV and current density of 7.34 mA/cm2. Under tungsten light of 15 W illumination the system produced average voltages of 166.20 mV and current density of 5.48 mA/cm2. Finally, the solar cell was tested under 7 W-LED illumination that was calibrated to silicon solar cell equal to sun light of 1.5 AM (100 mW/cm2) resulted in efficiency of 0.027%.